Morphophysiological characterization of leaves and inflorescences of commercial mini chrysanthemum varieties - de Carvalho, Carolina Rodrigues Victor; Santos, Mirelle Nayana de Sousa; Mapeli, Ana Maria (Ornamental Horticulture, 2020)
Chrysanthemum is among the oldest plants cultivated by man, being widely cultivated in Brazil. In view of its economic importance and use in breeding, the present study aims to characterize mini chrysanthemum varieties, focusing on morphological and physiological parameters. Therefore, four varieties of mini chrysanthemums, in pots, were acquired in the local market: V1 - ‘Swifty Light Pink’ (purple), V2 - ‘Diablo Time’ (red), V3 - ‘White Cherie’ (white); V4 - ‘Giovanni’ (yellow), from which they were taken leaves and inflorescences samples for measurement of height, diameter and fresh mass, as well as to quantify the total soluble sugar (TSS, %), reducing sugar (RS, %), non-reducing sugar (NRS, %), anthocyanin and chlorophyll contents. Regarding the characterization of inflorescences, it was found that ‘Diablo Time’ had the largest diameter, height and fresh weight, in these last two cases not differing from ‘Giovanni’, which had lower anthocyanin content; while the highest values of carbohydrate content were found in ‘White Cherie’. In relation to the characterization of the leaves, ‘Giovanni’ had the largest dimensions, fresh mass and chlorophyll content. Already ‘Swifty Light Pink’ stood as to the sugar contents. Thus, it is clear that there are morphophysiological differences between the chrysanthemum mini varieties, which can contribute to breeding programs.